A sociology of queer implications? Methodological inquietudes and ethical involvements in the study of non-normative sexualities - RINALDI, CIRUS (Bagoas - Estudos gays: gêneros e sexualidades, 2018)
The article represents an epistemological and methodological enquiry on the use of qualitative research methods, and specifically ethnographical practice, in the study of non-normative sexualities. It will take mainly into account a series of ethnographic observations of an ongoing research project on male sex work in southern Italy.